Computing pharmacokinetic parameters from blood level--time data of equi-interval samplings - ZHOU Huai-wu (Acta Pharmacologica Sinica, 2016)
In pharmacokinetics, the method of residuals is commonly used for calculating pharmacokinetic parameters of drug. In the case of oral, intramuscular or intravenous administrations, the drug elimination rate constant(K) obtained by this method may contain significant errors which affect the accuracy of the drug absorption rate constant estimated, when Ka approach to K. This paper suggested a new method of pharmacokinetic experimental design and data-processing,that is,computing pharmacokinetic parameters of drugs from blood level-time data of equi-interval sampleings. Theoretical analysis and examples were given for one- or two-compartment open models after iv administration and for one-compartment open model after po or im admistrations. The results show that this method can ben used to calculate effectively pharmacokinetic parameters without the defects of the method of residuals.